2020
DOI: 10.5489/cuaj.6984
|View full text |Cite
|
Sign up to set email alerts
|

Case – 18F-DCFPyL-positron emission tomography/computed tomography (PET/CT) time of imaging

Abstract: NA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…PSMA PET/CT also has limitations in the detection of local recurrence since benign prostatic pathologies such as focal prostatitis, benign prostatic hyperplasia and even normal prostate can show areas of increased uptake (6,7). Some strategies such as interval increased activity on delayed PSMA PET/CT scan can suggest malignancy in equivocal cases (8). Also, studies have shown that imaging and biopsy results can evolve post-radiation (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…PSMA PET/CT also has limitations in the detection of local recurrence since benign prostatic pathologies such as focal prostatitis, benign prostatic hyperplasia and even normal prostate can show areas of increased uptake (6,7). Some strategies such as interval increased activity on delayed PSMA PET/CT scan can suggest malignancy in equivocal cases (8). Also, studies have shown that imaging and biopsy results can evolve post-radiation (9,10).…”
Section: Discussionmentioning
confidence: 99%